2002
DOI: 10.1140/epjb/e20020075
|View full text |Cite
|
Sign up to set email alerts
|

Failure time and critical behaviour of fracture precursors in heterogeneous materials

Abstract: The acoustic emission of fracture precursors, and the failure time of samples of heterogeneous materials (wood, fiberglass) are studied as a function of the load features and geometry. It is shown that in these materials the failure time is predicted with a good accuracy by a model of microcrack nucleation proposed by Pomeau. We find that the time interval δt between events (precursors) and the energy ε are power law distributed and that the exponents of these power laws depend on the load history and on the m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
89
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(96 citation statements)
references
References 22 publications
7
89
0
Order By: Relevance
“…In analogy to the study of critical phase transitions in statistical physics, it has been recently argued that the fracture of heterogeneous materials could be viewed as a critical phenomenon (Herrmann and Roux, 1990;Vanneste and Sornette, 1992;Lamaignere et al, 1996;Andersen et al, 1997;Sornette, 2000), either at laboratory scale (Petri et al, 1994;Guarino et al, 1998Guarino et al, , 2002 or at geophysical scales (Chelidze, 1982;Allegre et al, 1982;Sornette and Sornette, 1990;Diodati et al, 1991;Sornette and Sammis, 1995;Saleur et al, 1996a,b;Main, 1996;Bowman et al, 1998;Kossobokov et al, 1999). This result comes from different observations including power law scaling in space (fractals), time and energy, long-range correlations, or the divergence of the rate of energy dissipation near the critical point.…”
Section: Introductionmentioning
confidence: 99%
“…In analogy to the study of critical phase transitions in statistical physics, it has been recently argued that the fracture of heterogeneous materials could be viewed as a critical phenomenon (Herrmann and Roux, 1990;Vanneste and Sornette, 1992;Lamaignere et al, 1996;Andersen et al, 1997;Sornette, 2000), either at laboratory scale (Petri et al, 1994;Guarino et al, 1998Guarino et al, , 2002 or at geophysical scales (Chelidze, 1982;Allegre et al, 1982;Sornette and Sornette, 1990;Diodati et al, 1991;Sornette and Sammis, 1995;Saleur et al, 1996a,b;Main, 1996;Bowman et al, 1998;Kossobokov et al, 1999). This result comes from different observations including power law scaling in space (fractals), time and energy, long-range correlations, or the divergence of the rate of energy dissipation near the critical point.…”
Section: Introductionmentioning
confidence: 99%
“…The experiments show that the probability density N(ǫ) of microfractures with energy between ǫ and ǫ + dǫ, follows a powerlaw: N(ǫ) ∼ ǫ −β . Different materials are characterised by different values of β: 1.25 in paper [2], 1.3 in synthetic plaster [3], 1.51 in wood [4], 1.9 in fiberglass [5] and 1.5 in cellular glass [6]. On the other hand, the cumulative energy emitted while approaching the fracture also shows power-law in situations where stress is controlled.…”
mentioning
confidence: 99%
“…On the other hand, the cumulative energy emitted while approaching the fracture also shows power-law in situations where stress is controlled. For instance, in [4,5], it was found that…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Seismic activity is being monitored with high spatial and temporal resolution, but it is still unclear how the accumulated data can be used for predicting large seismic events [1]. In engineering constructions such as buildings, water dams, or mines [2][3][4], acoustic monitoring is used as an empirical method which provides remotely sensed information on the accumulation of damage. However, again no method is yet at hand which could reliably and accurately predict the imminent collapse of structures based on such data.…”
Section: Introductionmentioning
confidence: 99%